Communal Riots in India - Razia, Dr. (IJRDO-Journal of Applied Science, 2015)
The economic system of any country depends on the internal and external security of the people and the government, which make negative and positive impact on the society and their people. Likewise our nation’s economic security is also depends on the internal and external security, which affected the economy of our country. A significant factor affecting the economy of our country is communal riots. Due to this violence, internal and external security of the country is in danger and the country’s economy is getting affected. The article presents the consequences of communal riots which took place time to time in the country.